Tandem hydroformylation / Fischer indolization - Schmidt, Axel Matthias (Technische Universität Dortmund, 2006)
S. 179 - 185
synthesis of biologically relevant indoles under hydroformylation conditions
Keywords: Hydroformylation; Indole; Trytamine; Tandem reaction; 540